Phytotoxicity and Benzoxazinone Concentration in Field Grown Cereal Rye (Secale cereale L.) - C. La Hovary; D. A. Danehower; G. Ma; C. Reberg-Horton; J. D. Williamson; S. R. Baerson; J. D. Burton (International Journal of Agronomy)
Winter rye (Secale cereale L.) is used as a cover crop because of the weed suppression potential of its mulch. To gain insight into the more effective use of rye as a cover crop we assessed changes in benzoxazinone (BX) levels in rye shoot tissue over the growing season. Four rye varieties were planted in the fall and samples harvested at intervals the following spring. Two different measures of phytotoxic compound content were taken. Seed germination bioassays were used as an estimate of total phytotoxic potential. Dilutions of shoot extracts were tested using two indicator species to compare the relative toxicity of tissue. In addition, BX (DIBOA, DIBOA-glycoside, and BOA) levels were directly determined using gas chromatography. Results showed that rye tissue harvested in March was the most toxic to indicator species, with toxicity decreasing thereafter. Likewise the BX concentration in rye shoot tissue increased early in the season and then decreased over time. Thus, phytotoxicity measured by bioassay and BX levels measured by GC have a similar but not identical temporal profile. The observed decrease in phytotoxic potential and plant BX levels in rye later in the season appears to correlate with the transition from vegetative to reproductive growth.